Grain boundary relaxation and reconstruction: effect on local magnetic moment - Vitkovská, E.; Ballo, P. (Condensed Matter Physics, 2016)
We present a detailed numerical study on structure and local magnetic properties of 〈100〉 symmetric tilt grain boundaries in bcc-iron. Particular attention is paid to connection between type of grain boundary relaxation and local magnetic properties. Results from first principles calculation showed that grain boundary reconstruction leads to non-uniform distribution of local magnetic moments in grain boundary plane. This is in contrast with the result obtained in grain boundary plane, where simple relaxation is observed. Well optimized atomic configurations in the vicinity of the interface were achieved by simulated annealing optimization technique improved by combination with genetic algorithm. Ми представляємо детальне числове дослiдження структури i локальних магнiтних властивостей симетричних похилених зернинних меж 〈100〉 у залiзi з кубiчною об’ємоцентричною структурою. Особлива увага придiляється зв’язку мiж типом зернинномежової релаксацiї i локальними магнiтними властивостями. Результати першопринципних обчислень показали, що зернинномежова реконструкцiя приводить до неоднорiдного розподiлу локального магнiтного моменту в зернинномежовiй площинi. Це протирiчить результату, отриманому в зернинномежовiй площинi, де спостережено просту релаксацiю. Було досягнуто добре оптимiзованi атомнi конфiгурацiї поблизу межi роздiлу за допомогою комбiнацiї методу вiдпаленої оптимiзацiї з генетичним алгоритмом.